Comparative analysis of outcomes following craniotomy and expanded endoscopic endonasal approach resection of tuberculum sellae meningiomas: a single-institution study - Feng, Zhenguang; Li, Chuzhong; Cao, Lei; Liu, Chunhui; Qiao, Ning; Wu, Wentao; Ma, Guofo; Gui, Songbai (Frontiers in Neurology, 2023)
Background Traditionally, supratentorial craniotomy has been used to sever tuberculum sellae meningiomas (TSMs), but there has been a remarkably increasing tendency of extended endoscopic endonasal approach (EEEA) used to treat TSMs in the recent decade. Several documents have described the advantages and disadvantages of both approaches, but there is no consensus on whether one is superior to the other. Objective This study aimed to compare surgical outcomes between craniotomy and EEEA for TSMS treated at our institution. Methods From January 2015 to December 2021, a total of 84 cases of TSMs were included in this study. Cases were separated into two groups: the craniotomy group and the EEEA group. Their anamneses and surgical records were reviewed. Demographic data, presenting symptoms, tumor volume, extent of resection, visual outcomes, and follow-up data were tabulated. The Kaplan–Meier curves were constructed for the PFS for both cohorts. Results Complete data were available for 84 surgeries; 39 cases were treated via craniotomy, and 45 were treated via EEEA. Patient demographic data, pre-operative symptoms, and tumor characteristics were similar between the two cohorts. The extent of resection was similar between the two groups (GTR: 91.11% EEEA vs. 87.18% craniotomy; STR 8.89 vs. 12.82%, p = 0.91). There was no difference in visual outcomes between both groups (92.1 vs. 84.84%, p = 0.46). An increased rate of cranial nerve injury was noted in the craniotomy group (0 vs. 10.25%, p = 0.04). Post-operative CSF leak rate occurred in one patient in the EEEA group. The PFS curves (p = 0.52) and recurrence/progression rates (13.33 vs. 20.51%, p = 0.39) were similar between the two groups. Conclusion Both EEEA and craniotomy can successfully sever TSMs. The recurrence/progression rate and PFS appear to be similar between the two groups. Although there are no differences in EOR and visual outcomes between the two groups, there was a clear trend in the EEEA group to obtain a better outcome. CSF leakage was common in the EEEA cohort, whereas the rate of cranial nerve injury was found to be higher in the craniotomy cohort. We believe that our data support the conclusion that EEEA surgery is the preferred approach for the removal of TSMs.